2024
DOI: 10.1002/eat.24189
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid body weight predicts weight loss in both anorexia nervosa and atypical anorexia nervosa: Further support for a single underlying disorder

Johannes Hebebrand,
Jochen Seitz,
Manuel Föcker
et al.

Abstract: ObjectiveFor adolescents, DSM‐5 differentiates anorexia nervosa (AN) and atypical AN with the 5th BMI‐centile‐for‐age. We hypothesized that the diagnostic weight cut‐off yields (i) lower weight loss in atypical AN and (ii) discrepant premorbid BMI distributions between the two disorders. Prior studies demonstrate that premorbid BMI predicts admission BMI and weight loss in patients with AN. We explore these relationships in atypical AN.MethodBased on admission BMI‐centile < or ≥5th, participants included 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In the current study, we sought to provide further support for a homogenous conceptualization of AN and atypical AN by replicating and expanding upon Hebebrand and colleagues' parallel study (Hebebrand et al, 2024). Specifically, we assessed whether differentiating AN and atypical AN by clinical 'underweight' (i.e., BMI% < 5th) yields a skewed premorbid weight distribution in which youth with premorbid 'overweight/obesity' are disproportionally diagnosed with atypical AN versus AN.…”
Section: Ongoing Differentiation Of An and Atypical An Via Clinicalmentioning
confidence: 93%
See 4 more Smart Citations
“…In the current study, we sought to provide further support for a homogenous conceptualization of AN and atypical AN by replicating and expanding upon Hebebrand and colleagues' parallel study (Hebebrand et al, 2024). Specifically, we assessed whether differentiating AN and atypical AN by clinical 'underweight' (i.e., BMI% < 5th) yields a skewed premorbid weight distribution in which youth with premorbid 'overweight/obesity' are disproportionally diagnosed with atypical AN versus AN.…”
Section: Ongoing Differentiation Of An and Atypical An Via Clinicalmentioning
confidence: 93%
“…Notably, our use of midpoint BMI% to calculate premorbid BMI% differed from Hebebrand et al (2024) methodology, which calculated premorbid BMI% with (a) self-or parent reported premorbid weight prior to initial weight loss (kg); (b) self-or parent reported age at onset of initial weight loss; and (c) measured admission height. We examined correlations between our respective methodologies; in a random 10% of participants, premorbid BMI% values were calculated using Hebebrand's method and compared to premorbid midpoint BMI% data.…”
Section: Medical Chart Reviewmentioning
confidence: 99%
See 3 more Smart Citations